Analyzing Urban Travel Behavior Components in Tehran: Evidence from Iran - Dr. Alizadeh Suber; Dr. Faezeh Amir; Shafepour Nadaf (Al-Qanṭara, 2023)
This study aims to investigate the nature and characteristics of urban travel behaviour in the metropolitan region of Tehran, Iran's capital. To that end, we assessed six main Travel Behavior Components using the perspectives of 822 participants via a questionnaire survey. (TBCs)—that is, travel mode, travel time, travel location, travel frequency, travel choice, and travel purpose—through the lens of five distinct sociodemographic characteristics, namely, gender, age, family structure, educational and occupational groups. We analysed priorities and preferences related to TBCs across various social groups and explored the impact of preferences of different social groups on TBCs in the Tehran metropolitan area using SPSS26, MAXQDA, and Structural Equation Model (SEM) via AMOS software. The findings show that, first and foremost, the propensity Keywords: travel behavior; socio‐demographic characteristics; travel mode, and Iran